Exploring The Culinary Harmony of Squash and Pineapple Fusion in Cake Making - Conlu, Melinda O. (Future Science / FSH-PH Publications, 2024)
This experimental research aimed to formulate a cake made from the mixture of squash and pineapple. It utilized a Completely Randomized Design (CRD) with three (3) treatments and evaluated as to its sensory qualities and acceptability in terms of appearance, aroma, taste and texture by 40 evaluators composed of experts and consumers. Score cards with Nine (9) Point Hedonic Scale was used to evaluate the product. The mean and Analysis of Variance (ANOVA) were used to analyze the data with alpha set at 0.01 level of significance. Findings on the evaluation of sensory qualities and acceptability of the three (3) treatments showed that Treatment C with the proportion of 100grams combination of squash and pineapple showed the most preferred among the treatments with verbal interpretation of “Liked Extremely” in terms of appearance, aroma, taste and texture based on the evaluation of experts and consumers. The finding led to the conclusion that the squash-pineapple cake was acceptable in terms of its appearance, aroma, taste and texture.